The Invisible Cities. - Gurewitz, David; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Petach Tikwa : Yad Lebanim, 1994)
Rimon, Lee ; Cedar, Mira ; Feldman, Dorit ; Ozeri, Yigal ; Salama-Ortar, Ilana ; Mehler, Motti ; Leinman, Colette
The Invisible Cities, Yad Lebanim Museum, Petach Tikwa, 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek